CEO power, innovative investment and family board involvement: An empirical study of Chinese family SMEs - Kaiyang Sun (Cogent Business & Management, 2022)
Drawn the socio-emotional wealth perspective, this paper investigates the relationship among CEO power, innovative investment and family board involvement in family enterprises. Secondary data on listed Chinese family small- and medium-sized enterprises from 2015 to 2019 was accessed via the China Stock Market and Accounting Research database and analysed using hierarchical multiple regression. The findings suggest a significant positive effect of CEO power on innovative investment in Chinese family SMEs. This study also found the moderating effect of family board involvement could inhibit the positive relationship between CEO power and family SMEs' innovativeinvestment. Further, compared with hiring external professional managers as CEO, the inhibitory moderating effect of family board involvement is more significant when a family member is appointed as a CEO in family SMEs. In order to better adapt to the increasingly competitive market environment, the findings of this paper suggest that internal family board members should appropriately reduce their influence on the CEO power to stimulate Chinese family SMEs to conduct more innovative investment for their long-term prosperity.
Keywords: 650; Family firms; CEO power; CEO source; family board; family involvement; innovative investment; R&D investment; small and medium-sized enterprises